Thermal transport characteristics in diamond/SiC composites via molten Si infiltration. Issue 12 (15th June 2021) - Zhang, Yuying; Wang, Tianshi; Hsu, Chun-Yen; Wynn, Justin; Karandikar, Prashant; Feser, Joseph P.; Ni, Chaoying
Abstract: Heat dissipation remains a critical challenge in optical and electronic devices and diamond/SiC composite is the premiere material solution because of its outstanding thermal and mechanical properties. Si liquid infiltration is one of the most promising techniques to fabricate fully dense diamond/SiC composites with desired phase structures and exceptional properties. In this study, the thermal conductivity from room temperature to 1000 °C was investigated for the diamond/SiC composites fabricated by a liquid Si infiltration method. The experimental thermal measurement shows a good agreement with the computational solution obtained by solving the Boltzmann transport equation. The results suggest a strong correlation between the composite thermal conductivity and diamond volume percentage. A level-off of the thermal conductivity at high diamond content reflects increased thermal resistance. In addition, the annealing effect on the composite thermal conductivity as well as the thermal stability were evaluated.